2015
DOI: 10.1007/s00192-015-2888-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mixed, stress, and urgency urinary incontinence in middle-aged/older women: the importance of incontinence history

Abstract: Introduction & Hypothesis Urinary incontinence (UI) is common and the relationship between its subtypes is complex. Our objective was to describe the natural history and predictors of incontinence subtypes, Stress, Urgency and Mixed, in mid-aged and older U.S. women. We hypothesized that past UI subtype history predicted future UI subtype status and sought to determine the extent to which this occurred. Methods We analyzed longitudinal urinary incontinence data in 10,572 community-dwelling women ≥50 in the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 18 publications
6
60
2
5
Order By: Relevance
“…Waetjen et al noted that a BMI increase of 5 kg/m 2 increased SUI by 30% and UUI by 15%. Also in elderly women, obesity is reported as an incontinence predictor and BMI had a specific effect on mixed urinary incontinence prediction . Chronically increased BMI is also associated with an elevated risk of UI in later life.…”
Section: Obesity and Ui: Clinical Viewmentioning
confidence: 94%
See 1 more Smart Citation
“…Waetjen et al noted that a BMI increase of 5 kg/m 2 increased SUI by 30% and UUI by 15%. Also in elderly women, obesity is reported as an incontinence predictor and BMI had a specific effect on mixed urinary incontinence prediction . Chronically increased BMI is also associated with an elevated risk of UI in later life.…”
Section: Obesity and Ui: Clinical Viewmentioning
confidence: 94%
“…Also in elderly women, obesity is reported as an incontinence predictor and BMI had a specific effect on mixed urinary incontinence prediction. 22 Chronically increased BMI is also associated with an elevated risk of UI in later life. Symptom severity also appears to worsen with the duration of increased BMI status, again confirming the detrimental effect of obesity on continence.…”
Section: Translational Viewmentioning
confidence: 99%
“…Longitudinal studies focusing on these different major categories of UI are extremely rare. 13,14 Only cohort studies, however, can illuminate the epidemiology of UI by clarifying the chronology and direction of the effects of the risk factors identified in cross-sectional studies. Longitudinal studies thus make it possible to better provide the causality of the factors studied.…”
Section: Introductionmentioning
confidence: 99%
“…The unprecedented growth of the elderly population in the western world highlights the importance of studying the long‐term outcomes of the interventions used for treatment of chronic conditions, including urinary incontinence (UI). In 2016, a large epidemiology study in the United States showed prevalence in UI of 19‐26% and increasing with age; this was most apparent for urgency urinary incontinence (UUI) and mixed urinary incontinence (MUI). Interestingly, the prevalence of stress urinary incontinence (SUI) did not seem to increase with age in this study.…”
Section: Introductionmentioning
confidence: 99%